2020
DOI: 10.3389/fpsyg.2020.00330
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Speaking Proficiency: A Narrative Review of Speaking Assessment Research Within the Argument-Based Validation Framework

Abstract: This paper provides a narrative review of empirical research on the assessment of speaking proficiency published in selected journals in the field of language assessment. A total of 104 published articles on speaking assessment were collected and systematically analyzed within an argument-based validation framework (Chapelle et al., 2008). We examined how the published research is represented in the six inferences of this framework, the topics that were covered by each article, and the research methods that we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 64 publications
0
22
0
1
Order By: Relevance
“…Bachman ( 2005 ) stressed that, before using an assessment for decision-making purposes, a validity argument should be fully fledged in terms of evidence supporting test developers' claims. On the other hand, empirical validation studies have demonstrated that collecting such evidence to establish an all-encompassing validity argument is an arduous and logistically complex task (Chapelle et al, 2008 ; Aryadoust, 2013 ; Fan and Yan, 2020 ). We are, hence, keen to determine the extent to which language assessment and SLA studies involving measurement and assessment have fulfilled the requirements of validation in the research clusters that are identified through DCA.…”
Section: Introductionmentioning
confidence: 99%
“…Bachman ( 2005 ) stressed that, before using an assessment for decision-making purposes, a validity argument should be fully fledged in terms of evidence supporting test developers' claims. On the other hand, empirical validation studies have demonstrated that collecting such evidence to establish an all-encompassing validity argument is an arduous and logistically complex task (Chapelle et al, 2008 ; Aryadoust, 2013 ; Fan and Yan, 2020 ). We are, hence, keen to determine the extent to which language assessment and SLA studies involving measurement and assessment have fulfilled the requirements of validation in the research clusters that are identified through DCA.…”
Section: Introductionmentioning
confidence: 99%
“…To sum up, although numerous factors such as rating scales, task characteristics, and rater effects have been reported in previous studies as influential variables to speaking assessment quality (Fan & Yan, 2020;McNamara et al, 2019;O'Sullivan, 2002), very few studies provide insights into test examiners' perspectives about these factors. Besides, qualitative aspects of VSTEP have not been extensively reported in the literature (Nguyen, 2015).…”
Section: Factors Relevant To Oral Performancementioning
confidence: 98%
“…Speaking assessment practices can be affected by diverse factors such as task and interlocutor characteristics, test validity and reliability, assessment criteria (Fan & Yan, 2020;Kang & Wang, 2014), rater effects ( McNamara et al, 2019), and rater training (Kang et al, 2019). Studies have shown that interaction tasks involving interactions with examiners can be unnatural compared to paired or oral group tests, in which the test taker interacts Pertanika J.…”
Section: Factors Relevant To Oral Performancementioning
confidence: 99%
“…To collect papers, the method of preferred reporting items for systematic reviews and meta-analyses (PRISMA) was adopted ( Moher et al, 2009 ; Shintani and Wallace, 2014 ; Fan and Yan, 2020 ). The literature search was intended to identify published studies investigating the validity issues of language tests for immigration purposes.…”
Section: Selection Of Studiesmentioning
confidence: 99%